2011
DOI: 10.4025/actascibiolsci.v33i3.7725
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the efficiency of two bioindicators for determining surface water quality in an urban environment

Abstract: ABSTRACT. This study evaluated the efficiency of two bioindicators, fecal coliforms and ecotoxicity tests, set out in CONAMA Resolution 274/00 and CONAMA Resolution 357/05, in assessment of water quality. For this study, Lake Paranoá, Federal District of Brazil, was chosen, since it is a water body directly contaminated by effluents from a sewage treatment plant. Four sampling points were chosen in accordance with the map of recreational water quality published weekly by CAESB/DF, after analysis of fecal colif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
1
0
4
Order By: Relevance
“…However, in rural areas Ragosta et al (2010) have confirmed a strong association between a decrease in the riparian canopy cover and an increase in fecal bacteria in surface runoff. Oliveira-Filho et al (2011) also noted a higher efficiency in using E. coli as a bioindicator than in assays with C. dubia when urban pollution was evaluated in Lake Paranoá in Brasília, Brazil.…”
Section: Sobradinho River (Urban Area)mentioning
confidence: 97%
“…However, in rural areas Ragosta et al (2010) have confirmed a strong association between a decrease in the riparian canopy cover and an increase in fecal bacteria in surface runoff. Oliveira-Filho et al (2011) also noted a higher efficiency in using E. coli as a bioindicator than in assays with C. dubia when urban pollution was evaluated in Lake Paranoá in Brasília, Brazil.…”
Section: Sobradinho River (Urban Area)mentioning
confidence: 97%
“…Resultado esse comprovado por Takenaka et al (2006) que analisaram as águas dos reservatórios de Anhumas e Cruzes, no município de Araraquara, e observaram que as amostras de água além de não causarem toxicidade ao organismo-teste promoveram um aumento na taxa de natalidade e, atribuíram esse fato a maior disponibilidade de alimento no corpo hídrico. Oliveira-filho et al (2011) também atribuiu a ausência de toxicidade, na maioria dos ensaios, com o microcrustáceo C. dubia, ao efluente doméstico, pois os efluentes são extremamente variáveis em sua composição e afirma que o monitoramento completo deve continuar, em relação as constantes mudanças em geral encontrado na composição de esgoto.…”
Section: Discussionunclassified
“…A área analisada possui atividades agropastoris e a expansão da área urbana, porém não é um local de despejos industriais e Oliveira-Filho et al (2011), afirma que a presença de produtos químicos na água é o principal fator para a ocorrência de efeitos tóxicos em C. dubia e Danio rerio. Hu et al (2012) conclui que a sinergia das substâncias químicas pode trazer um efeito tóxico para espécies aquosas, como C. dubia, através da captação de partículas.…”
Section: Discussionunclassified
“…Resultado esse comprovado por Takenaka et al (2006) que analisaram as águas dos reservatórios de Anhumas e Cruzes, no município de Araraquara, e observaram que as amostras de água além de não causarem toxicidade ao organismo-teste promoveram um aumento na taxa de natalidade e, atribuíram esse fato a maior disponibilidade de alimento no corpo hídrico. Oliveira-filho et al (2011) também atribuiu a ausência de toxicidade, na maioria dos ensaios, com o microcrustáceo C. dubia, ao efluente doméstico, pois os efluentes são extremamente variáveis em sua composição e afirma que o monitoramento completo deve continuar, em relação as constantes mudanças em geral encontrado na composição de esgoto.…”
Section: Discussionunclassified